Avaliação da prevalência de Carbapenemases em amostras de Enterobactérias isoladas no complexo Hospital São Paulo/UNIFESP - Nicoletti, Adriana Giannini [UNIFESP] (2010)
Objective: The aim of this study was to evaluate the presence of carbapenemases in Enterobacteriaceae isolated in Hospital São Paulo Complex (UNIFESP) between June and July 2008. Methods: The presence of MBL- and KPC-encoding genes was investigated by PCR. A screening test was conducted to detect isolates non-susceptible to at least one carbapenem. The antimicrobial susceptibility profile was determined by the CLSI agar dilution method for all isolates non-susceptible to carbapenens. Modified Hodge test and the detection of β-lactam hydrolysis, carried out by spectrophotometer assays, were conducted for the isolates that confirmed to be non-susceptible to at least one carbapenem. The production of ESBL or plasmid-mediated AmpC β-lactamases was investigated by phenotypic tests and their respective encoding genes were investigated by PCR. Amplifications of ompK35 and ompK36 genes were performed to evaluate whether outer membrane proteins (OMPs)-encoding genes were disrupted or missing. Clonality among isolates non-susceptible to carbapenens was assessed by automated ribotyping. The incompatibility groups of plasmids were determined by PCR-based replicon typing as previously described by Carattoli et al., 2005 and Götz et al., 1996, for 10% of the isolates included in this study and of 7 MBL-producing control strains. Results: 450 Enterobacteriaceae clinical isolates were investigated. The MBL and KPC-encoding genes were not detected in any isolate. The susceptibility rate to meropenem, imipenem and ertapenem were 99.3%, 98.4% and 98%, respectively. Overall, 2.9% of the isolates were classified as nonsusceptible to carbapenens. Of those, only 45.5% (5 K. pneumoniae isolates) confirmed to be non-susceptible to at least one carbapenem by the agar dilution technique. The modified Hodge test and the β-lactam hydrolysis by spectrophotometer assays did not detect carbapenemase production in these isolates. The mechanisms conferring reduced susceptibility to carbapenems among these isolates are the production of ESBL (blaCTX-M, blaSHV and/or blaTEM) associated with altered OMPs (n=4), or only altered OMPs (n=1). Three K. pneumoniae isolates non-susceptible to carbapenens were clustered in one ribogroup. The determination of plasmids’ incompatibility group was carried out to verify if transmission of MBL-encoding genes was prevented due to incompatibility between plasmids occurring in the Enterobacteriaceae clinical isolates studied and those carrying MBL-encoding genes. The incompatibility group of 58.5% of isolates could not be determined due to lack of amplification. Among the remaining isolates the incompatibility groups I1, FIA, FIB, FIC, FrepB, FIIs, P, K/B, N, L/M, A/C and Q were found. Among the MBL producers, the incompatibility group could be determined only for two IMP-1 producers, S. marcescens (IncQ) and E. cloacae (IncQ and IncA/C). Conclusions: While MBL-production is highly prevalent among P. aeruginosa and Acinetobacter spp. clinical isolates from Hospital São Paulo, Enterobacteriaceae isolates nonsusceptible to carbapenens due to carbapenemase production were not detected. In contrast, reduced susceptibility to carbapenems occurred due to the association of β-lactamase production with altered OMPs. The hypothesis that incompatibility between plasmids could have prevented transmission of MBL-encoding genes from non-fermenter rods to Enterobacteriaceae could not be confirmed since most strains presented non-typable plasmid content.